P266 The impact of vedolizumab and ustekinumab on arthropathy and arthralgia in IBD patients: a real-life multicentric cohort study. (27th May 2021) - Truyens, M; De Galan, C; Peeters, H; Mesonero Gismero, F; Elorza, A; Torres, P; Vandermeulen, L; Jauregui Amezaga, A; Ferreiro-Iglesias, R; Holvoet, T; Zabana, Y; Peries Reverter, L; et al.
Abstract: Background: Extra-intestinal manifestations (EIM) are frequently reported in inflammatory bowel diseases (IBD). Although the efficacy of TNF inhibitors is well documented, data regarding the effect of vedolizumab (VDZ) and ustekinumab (UST) are limited. Theoretically, the advantage of VDZ, i.e. gut-selectivity, may reduce the efficacy on EIM while the systemic effect of UST may be of benefit. Therefore, we evaluated the differences in new onset and evolution of EIM during both treatments. Methods: An international multicentric retrospective study was performed on IBD patients who started VDZ or UST between May 2010 and December 2020. EIM were assessed at baseline and during follow-up. Arthropathy was defined as joint inflammation (arthritis/sacroiliitis) and arthralgia as articular pain without confirmed inflammation. Skin EIM included erythema nodosum (EN), pyoderma gangrenosum (PG) and Sweet syndrome. Ocular EIM included (epi)scleritis and uveitis. Uni- and multivariate analyses were performed. Results: In total 856 patients were included: 528 treated with VDZ and 328 with UST. At baseline, arthropathy was more prevalent in UST treated patients (12.2% vs 7.2%; p=0.037; Table 1). No differences in rates of new onset (Fig 1) or evolution of pre-existing arthropathies could be identified between VDZ and UST. In multivariate analyses new onset arthropathy was not associated with smoking, IBD type, sex nor studied biological. In 5 out of 48 (10.4%) VDZ patients and 2 of 46 (4.3%) UST patients with either pre-existing or new arthropathy, treatment was stopped due to articular disease (difference not significant). In contrast, new arthralgia onset within 1 year of follow-up was significantly associated with VDZ treatment (OR 2.1 (1.1–4.0); p=0.022; Fig 1). Arthralgia was the reason to stop treatment in 2 of 87 (2.3%) VDZ patients and never in UST patients. Beside joint EIM, 2 patients developed EN, 1 PG and 1 episcleritis during VDZ treatment. Under UST treatment 1 patient developed EN. No patients developed new Sweet syndrome, scleritis nor uveitis. Conclusion: No differences in the rate of new arthropathy onset were observed between VDZ and UST. In contrast, VDZ treatment did increase the risk of new onset arthralgia.